2021
DOI: 10.1016/j.ajic.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers experience of working during the COVID-19 pandemic: A qualitative study

Abstract: Highlights COVID-19 pandemic caused crucial changes in work and personal life of healthcare providers. Healthcare providers are the backbone of healthcare systems and their mental health is the Achilles heel in the fight against COVID-19 The impacts of COVID-19 pandemic on work and personal life of healthcare providers life of healthcare providers is unknown Working in the pandemic era is a unique experience that may happen in the workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
297
2
25

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(365 citation statements)
references
References 19 publications
41
297
2
25
Order By: Relevance
“…These authors developed a three-level model: early exposure, with high levels of fear, anxiety and loss of control; peak of the crisis, which featured feelings of helplessness, hopelessness and depression; and long-term effects, with symptoms of post-traumatic stress disorder (PTSD) and reappearance of fears. Compared with Eftekhar Ardebili et al ’s 22 model, we found that during early exposure most participants had no sense about the COVID-19 epidemic and thus experienced few negative emotions. However, they tremendously suffered psychological pain during the peak of the crisis with massive infections and deaths of patients and colleagues.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…These authors developed a three-level model: early exposure, with high levels of fear, anxiety and loss of control; peak of the crisis, which featured feelings of helplessness, hopelessness and depression; and long-term effects, with symptoms of post-traumatic stress disorder (PTSD) and reappearance of fears. Compared with Eftekhar Ardebili et al ’s 22 model, we found that during early exposure most participants had no sense about the COVID-19 epidemic and thus experienced few negative emotions. However, they tremendously suffered psychological pain during the peak of the crisis with massive infections and deaths of patients and colleagues.…”
Section: Discussioncontrasting
confidence: 80%
“…While these emotions may be mitigated or exacerbated by work experience, environment and health status, participants’ reports suggest these experiences are pervasive. Eftekhar Ardebili et al 22 showed how emotions and feelings developed with the time of evolution of the pandemic. These authors developed a three-level model: early exposure, with high levels of fear, anxiety and loss of control; peak of the crisis, which featured feelings of helplessness, hopelessness and depression; and long-term effects, with symptoms of post-traumatic stress disorder (PTSD) and reappearance of fears.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their prior experiences, reframing of hardships was a vital factor. Few studies of resilience and resources in HCWs done earlier have identified work as “personal gratification” and “doctor’s duty as a resilience among challenges” in HCWs ( Ardebili et al, 2020 ; Liu et al, 2020 ). The latter study though done on a much smaller sample, was one of the first to identify that a physician’s “training, oaths, and values” were related to coping and resilience in such crisis situations.…”
Section: Discussionmentioning
confidence: 99%